2014
DOI: 10.1155/2014/678407
|View full text |Cite
|
Sign up to set email alerts
|

On Isometric Extension in the Spacesn(H)

Abstract: We study the problem of isometric extension on a sphere of the spacesn(H). We give an affirmative answer to Tingley’s problem in the spacesn(H).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…He dealt with C 0 (Ω), the space of all complex-valued continuous functions on a locally compact Hausdorff space Ω which vanish at infinity. A considerable number of interesting results have shown that Tingley's problem has a positive solution in ℓ p spaces, L p spaces, C 0 (Ω) spaces, certain finite dimensional Banach spaces, and so on [7,8,10,11,13,15,16,26,27,28,29,30,34,53,54,56,58,59,62,67,68,69,70,71,72,74,76].…”
Section: Introductionmentioning
confidence: 99%
“…He dealt with C 0 (Ω), the space of all complex-valued continuous functions on a locally compact Hausdorff space Ω which vanish at infinity. A considerable number of interesting results have shown that Tingley's problem has a positive solution in ℓ p spaces, L p spaces, C 0 (Ω) spaces, certain finite dimensional Banach spaces, and so on [7,8,10,11,13,15,16,26,27,28,29,30,34,53,54,56,58,59,62,67,68,69,70,71,72,74,76].…”
Section: Introductionmentioning
confidence: 99%
“…Kadets and Martin in [6] proved that any surjective isometry between unit spheres of finite-dimensional polyhedral Banach spaces has a linear isometric extension to the whole space. See also [2,3,4,5,9,11,12] for some related results.…”
Section: Introductionmentioning
confidence: 99%